How mountains are made - Zoehfeld, Kathleen Weidner; Hale, James Graham (New York, NY : HarperCollins, 1995)
The ocean floor and all continents rest on huge plates that make up the earth's outer shell. Scientists believe it is the movement of plates that causes mountains and volcanoes to form
620
Accelerated Reader AR
Keywords: Mountains; Geology